Implikasi Putusan Mahkamah Agung Terhadap Penggantian Antar Waktu Calon Anggota Legislatif Terpilih Meninggal Dunia - Ahmad Zain; Ismail Hasani; Muhammad Ishar Helmi (JOURNAL of LEGAL RESEARCH, 2020)
This paper examines the Judges' Considerations in the Supreme Court's Decision Number 57/P/HUM/2019 regarding the replacement between the time the elected candidate dies based on the General Election Commission and the Indonesian Democratic Party of Struggle. As well as analyzing the contents of the Supreme Court's Decision Related to the Interim Replacement Polemic. The method used is a normative legal research method with a statutory approach and a conceptual approach. The results show that there are implications regarding Decision Number 57/P/HUM/2019 due to the confusion of meaning in the Supreme Court's Decision so that there are multiple interpretations for the applicant and the respondent. Then, regarding the interim replacement mechanism, which basically has the right to nominate a replacement candidate from time to time, political parties have been ruled out by the general election commission because the proposal is against the law. Then the interim replacement candidate is based on the determination of the general election commission based on the provisions in the UUMD3.